Care needs of patients with chronic wounds for implementing a virtual care program: A qualitative study - Nasib Babaei; Vahid Zamanzadeh; Leila Valizadeh; Mojgan Lotfi; Marziyeh Avazeh (PLoS ONE, 2025)
Introduction Chronic and complex wounds are serious public health problems worldwide. Given the time-consuming nature of chronic wound healing and the need for long-term follow-up, a virtual care approach can effectively manage these patients. Identifying the care needs of patients with chronic wounds is key to successfully managing their care remotely. This study aimed to identify the care needs of patients with chronic wounds for implementing a virtual care program to manage this group of patients remotely. Methods This descriptive qualitative study was conducted using a conventional content analysis approach in wound care clinics of East Azerbaijan Province (northwestern Iran). Data were collected through six focus group discussions with wound therapists and six semi-structured individual interviews with patients with chronic wounds. Participants were recruited using purposive sampling. The data were analyzed by MAXQDA 10 software. Results After analyzing the data, the most important care needs of patients with chronic wounds for implementing a virtual care program were identified into three main categories, including the need for awareness-raising, needs related to health dimensions, and the need for specialized financial support (insurance). Conclusion The findings of this study indicated that the successful implementation of a virtual care program for patients with chronic wounds requires addressing three core needs: enhancing patients’ awareness regarding wound management, attending to their physical, emotional, and social health dimensions, and providing financial support through insurance coverage for wound care services. Addressing these needs can significantly improve the quality of care and therapeutic outcomes for patients in a virtual care setting.